Homocysteine induces caspase activation by endoplasmic reticulum stress in platelets from type 2 diabetics and healthy donors - Zbidi, Hanene; Redondo, Pedro C.; López, Jose J.; Bartegi, Aghleb; Salido, Gines M.; Rosado, Juan A. (Thrombosis and Haemostasis, 2010)
Diabetes mellitus is a disease characterised by hyperglycaemia and associated with several cardiovascular disorders, including angiopathy and platelet hyperactivity, which are major causes of morbidity and mortality in type 2 diabetes mellitus. In type 2 diabetic patients, homo-cysteine levels are significantly increased compared with healthy subjects. Hyperhomocysteinaemia is an independent risk factor for macro-and microangiopathy and mortality. The present study is aimed to investigate the effect of homocysteine on platelet apoptosis. Changes in cytosolic or intraluminal free Ca2+ concentration were determined by fluorimetry. Caspase activity and phosphorylation of the eukaryotic initiation factor 2α (eIF2α) were explored by Western blot. Our results indicate that homocysteine releases Ca2+ from agonist sensitive stores, enhances eIF2α phosphorylation at Ser51 and activates caspase-3 and -9 independently of extracellular Ca2+. Homocysteine induced activation of caspase-3 and -9 was abolished by salubrinal, an agent that prevents endoplasmic reticulum (ER) stress-induced apoptosis. Homo-cysteine-induced platelet effects were significantly greater in type 2 diabetics than in healthy subjects. These findings demonstrate that homocysteine induces ER stress-mediated apoptosis in human platelets, an event that is enhanced in type 2 diabetic patients, which might be involved in the pathogenesis of cardiovascular complications associated with type 2 diabetes mellitus.
Keywords: Homocysteine; ER stress; caspases; apoptosis; diabetes mellitus